2016
DOI: 10.1038/srep26065
|View full text |Cite|
|
Sign up to set email alerts
|

Spatial organization of heterologous metabolic system in vivo based on TALE

Abstract: For years, prokaryotic hosts have been widely applied in bio-engineering. However, the confined in vivo enzyme clustering of heterologous metabolic pathways in these organisms often results in low local concentrations of enzymes and substrates, leading to a low productive efficacy. We developed a new method to accelerate a heterologous metabolic system by integrating a transcription activator-like effector (TALE)-based scaffold system into an Escherichia coli chassis. The binding abilities of the TALEs to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…Lee et al exhibited the great potential of cytoscaffold for enzyme organization [ 11 ]. Furthermore, in addition to protein scaffolds, DNA scaffolds [ 12 , 13 ] and lipid-containing scaffolds [ 14 ] are also applied to improve the pathway efficiency. In addition to scaffolds, enzymes were also located to bacterial microcompartments (MCPs), such as ethanolamine utilization (Eut) [ 15 ] and 1,2-propanediol utilization (Pdu) MCPs for similar purposes [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Lee et al exhibited the great potential of cytoscaffold for enzyme organization [ 11 ]. Furthermore, in addition to protein scaffolds, DNA scaffolds [ 12 , 13 ] and lipid-containing scaffolds [ 14 ] are also applied to improve the pathway efficiency. In addition to scaffolds, enzymes were also located to bacterial microcompartments (MCPs), such as ethanolamine utilization (Eut) [ 15 ] and 1,2-propanediol utilization (Pdu) MCPs for similar purposes [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Using plasmid DNA as a scaffold, enzymes were proved to be colocalized around the plasmid. An approximately tenfold improvement on the productivity of an indole-3-acetic synthetic pathway in E. coli was also reported [ 41 ]. Compared to the ZFN approach, the TALEN technique provides a more efficient and practical approach for the clustering of multienzymes in vivo given its simpler design, higher specificity and lower toxicity [ 42 ].…”
Section: Genome-editing Techniques: New Hints For Developing Spatial mentioning
confidence: 99%
“…Determining how to apply the in vitro model of DNA scaffolds to the internal environment is a new challenge for researchers. So far, researchers have begun to use the characteristics of specific bindings of nucleic acid binding proteins (such as ZFPs and TALEs) and nucleotide sequences to realize the assembly of pathway enzymes [81][82][83][84][85][86][87]. For example, through fusing glucosamine-6-phosphate synthase (GlmS) and GlcNAc (N-acetylglucosamine)-6-phosphate N-acetyltransferase (GNA1) with the zinc finger proteins ADB3 and ADB2 by pHT plasmid, respectively, Liu and co-workers successfully constructed a DNA-guided scaffold system to modulate the activities of GlmS and GNA1 ( Figure 2), and they found that the co-location and control of the stoichiometric ratios of GlmS and GNA1 significantly increased the GlcNAc titer from 1.83 to 4.55 g/L in a shake flask [84].…”
Section: Nucleic Acid Scaffoldmentioning
confidence: 99%